Simultaneous chromatic and luminance human electroretinogram responses - Parry, Neil R. A.; Murray, Ian J.; Panorgias, Athanasios; Mckeefry, Declan J.; Lee, Barry B.; Kremers, Jan (The Journal of Physiology, 2012)
The parallel processing of information forms an important organisational principle of the primate visual system. Here we describe experiments which use a novel chromatic-achromatic temporal compound stimulus to simultaneously identify colour and luminance specific signals in the human electroretinogram (ERG). Luminance and chromatic components are separated in the stimulus; the luminance modulation has twice the temporal frequency of the chromatic modulation. ERGs were recorded from four trichromatic and two dichromatic subjects (1 deuteranope and 1 protanope). At isoluminance, the fundamental (first harmonic) response was elicited by the chromatic component in the stimulus. The trichromatic ERGs possessed low-pass temporal tuning characteristics, reflecting the activity of parvocellular post-receptoral mechanisms. There was very little first harmonic response in the dichromats' ERGs. The second harmonic response was elicited by the luminance modulation in the compound stimulus and showed, in all subjects, band-pass temporal tuning characteristic of magnocellular activity. Thus it is possible to concurrently elicit ERG responses from the human retina which reflect processing in both chromatic and luminance pathways. As well as providing a clear demonstration of the parallel nature of chromatic and luminance processing in the human retina, the differences that exist between ERGs from trichromatic and dichromatic subjects point to the existence of interactions between afferent post-receptoral pathways that are in operation from the earliest stages of visual processing.
EVALuna2:21088